Mining urban data (part A). (December 2015) - Katakis, Ioannis
Abstract: Modern cities are flooded with data. New information sources like public transport and wearable devices provide opportunities for novel applications that will improve citizens׳ quality of life. From a data science perspective, data emerging from smart cities give rise to a lot of challenges that constitute a new inter-disciplinary field of research. This article introduces the first part of a special issue on the topic 'Mining Urban Data' published in the journal Information Systems.